Governança corporativa no setor bancário brasileiro: a transparência voluntária de informações - Ribeiro, Wesley Luiz (2017)
The main objective of this work is to analyze the applied level of voluntary transparency of information in the Brazilian banking sector, as well as to verify if there is a difference of this level between major and minor banks, between public and private banks or between private banks with national control and with foreign control, justified by the importance of this sector to the country’s economy, from the viewpoint of its significant representativeness of inves-tors. The work is supported by a theoretical survey about corporate governance and voluntary transparency of information, as well as empirical research on these themes in the banking sec-tor. The research methodology nature was descriptive with quantitative method, it was applied content analysis in the public documents collected for the study, based on the Basel Commit-tee’s recommendations of transparency for banks. The main result was the level of banks ad-herence to recommendations of voluntary transparency of information, highlighting the cate-gories of "basic business, management and corporate governance informations" and "consoli-dated disclosure of information" as the least disclosed. Another important result is that there is no statistical evidence to prove the difference in the average of items disclosed between the largest and smallest banks or between public and private banks, however, private banks with national control, statistically, have a higher level of adherence to private banks with foreign control